Production efficiency and profit taxation - Stéphane Gauthier; Guy Laroque (Institute for Fiscal Studies (IFS), 2018)
Consider a simple general equilibrium economy with one representative consumer, a single competitive firm and the government. Suppose that the government has to finance public expenditures using linear consumption taxes and/or a lump-sum tax on profits redistributed to the consumer. We show that, if the tax rate on profits cannot exceed 100 percent, one cannot improve upon the second-best optimum of an economy with constant returns to scale by using a less efficient profit-generating decreasing returns to scale technology.
Keywords: H21; 330; optimal taxation; taxation of profits; production efficiency